Computer-aided detection for the identification of pulmonary nodules in pediatric oncology patients: initial experience. - Helm EJ; Silva CT; Roberts HC; Manson D; Seed MT; Amaral JG; Babyn PS; Helm, Emma J; Silva, Cicero T; Roberts, Heidi C; Manson, David; Seed, Mike T M; et al. (Pediatric Radiology, 2009)
Background: Computer-aided detection (CAD) has been shown to increase the sensitivity for detection of pulmonary nodules in adults. This study reports initial findings utilizing a CAD system for the detection of pediatric pulmonary nodules.Objective: To assess the performance of CAD and pediatric radiologists in the detection of pediatric pulmonary nodules.Materials and Methods: CT scans from a series of pediatric patients with known primary tumors and lung nodules were analyzed by four radiologists and a commercially available CAD system. IRB approval was obtained. Sensitivities were calculated for detection according to nodule size and location.Results: In 24 children (age 3-18 years) 173 nodules were identified. Overall the sensitivity of CAD was 34%, but the sensitivity of CAD for detection of nodules 4.0 mm or larger was 80%. Overall radiologist sensitivity ranged from 68% to 79%. There were 0.9 CAD false-positives and 0.3-2.4 radiologist false-positives per study.Conclusion: CAD in our pediatric oncology patients had good sensitivity for detection of lung nodules 4 mm and larger with a low number of false-positives. However, the sensitivity was considerably less for nodules smaller than 4 mm.